Kesiapan Guru PAUD Terhadap Transformasi Kurikulum Merdeka - Damar Damar (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2026)
The transformation of the Merdeka Curriculum at the Early Childhood Education (ECE) level requires teachers’ readiness as the main implementers of learning activities. This study aims to describe the level of ECE teachers’ readiness in facing the transformation of the Merdeka Curriculum, which includes pedagogical, professional, and psychological readiness. This research employed a descriptive quantitative approach involving ECE teachers who have implemented or are in the process of implementing the Merdeka Curriculum. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, and analyzed using descriptive statistics. The results indicate that, in general, ECE teachers are categorized as ready to face the transformation of the Merdeka Curriculum. Teachers demonstrate a good understanding of play-based and child-centered learning principles, although challenges remain in lesson planning and developmental assessment implementation. Supporting factors include institutional support and access to training, while inhibiting factors involve limited mentoring and administrative workload. The findings are expected to serve as a basis for policymakers in designing sustainable professional development programs for ECE teachers.